Supporters of domestic partner registery - Sahl, Ted (photographer):::Creator::::::::::::
BAYMEC members, including Wiggsy Sivertsen, standing front left, at the crowded Santa Clara Supervisor's hearing on the domestic partner bill. The audience is applauding the decision to approve the bill despite a 6-1 against by citizens who attended the hearing. One sign held by an audience member reads: "E[xpa?]nd [fam]ily [va]lues support domestic partner registry"